KEBIJAKAN HUKUM TERHADAP DISPENSASI PERKAWINAN BAGI ANAK DIBAWAH UMUR BERDASARKAN PENETAPAN PENGADILAN AGAMA SUMBER DI HUBUNGKAN DENGAN UNDANG-UNDANG NOMOR 17 TAHUN 2016 - Santoso, Wahyu; Aziz, Abdul; Setyawan, Edy (Fakultas Ilmu Sosial dan Humaniora, 2024)
The marriage age required by law is not absolute. However, the age standards for minors are different, because it turns out that these age standards can still be violated in the form of granting dispensations based on certain special considerations. However, Article 7 paragraph (2) states that if there is a deviation from the age provisions, the parents of the man or woman are permitted to apply for a marriage dispensation to the court for beneficial reasons and accompanied by supporting evidence. This marriage dispensation actually becomes a problem because of changes to the provisions on the age limit for marriage as stated in Law no. 16 of 2019 Article 7 paragraph (1) will seem pointless if in the end minors can marry legally with a marriage dispensation from the Court in the form of a determination as their legal agent. The marriage dispensation functions as legal maturity and a requirement for marriage for those who are not legally permitted to marry. Marriage dispensation is a voluntary case, namely a petition case in which there is no dispute, so it has no opponents and the legal product is in the form of a decree.